Metal‐Free Route for the Synthesis of 4‐Acyl‐1, 2, 3‐Triazoles from Readily Available Building Blocks. Issue 29 (10th June 2016) - Thomas, Joice; Goyvaerts, Vince; Liekens, Sandra; Dehaen, Wim
Abstract: Functionalized 1, 2, 3‐triazole heterocycles have been known for a long time and hold an extraordinary potential in diverse research areas ranging from medicinal chemistry to material science. However, the scope of therapeutically important 1‐substituted 4‐acyl‐1H‐1, 2, 3‐triazoles is much less explored, probably due to the lack of synthetic methodologies of good scope and practicality. Here, we describe a practical and efficient one‐pot multicomponent reaction for the synthesis of α‐ketotriazoles from readily available building blocks such as methyl ketones, N, N ‐dimethylformamide dimethyl acetal, and organic azides with 100 % regioselectivity. This reaction is enabled by the in situ formation of an enaminone intermediate followed by its 1, 3‐dipolar cycloaddition reaction with an organic azide. We effectively utilized the developed strategy for the derivatization of various heterocycles and natural products, a protocol which is difficult or impossible to realize by other means. Abstract : A metal‐free route towards therapeutically important 1‐substituted 4‐acyl‐1H‐1, 2, 3‐triazoles was accomplished using cheap and readily available ketones, N, N ‐dimethylformamide dimethyl acetal, and organic azides. This reaction is very general and was extended to the synthesis of various supramolecular receptors as well as to the functionalization of different natural products with α‐ketotriazoles, all of which are otherwise not possible by known methods.